Acute Respiratory Distress Syndrome Phenotypes - Reilly, John P.; Calfee, Carolyn S.; Christie, Jason D. (Seminars in Respiratory and Critical Care Medicine, 2019)
The acute respiratory distress syndrome (ARDS) phenotype was first described over 50 years ago and since that time significant progress has been made in understanding the biologic processes underlying the syndrome. Despite this improved understanding, no pharmacologic therapies aimed at the underlying biology have been proven effective in ARDS. Increasingly, ARDS has been recognized as a heterogeneous syndrome characterized by subphenotypes with distinct clinical, radiographic, and biologic differences, distinct outcomes, and potentially distinct responses to therapy. The Berlin Definition of ARDS specifies three severity classifications: mild, moderate, and severe based on the PaO2 to FiO2 ratio. Two randomized controlled trials have demonstrated a potential benefit to prone positioning and neuromuscular blockade in moderate to severe phenotypes of ARDS only. Precipitating risk factor, direct versus indirect lung injury, and timing of ARDS onset can determine other clinical phenotypes of ARDS after admission. Radiographic phenotypes of ARDS have been described based on a diffuse versus focal pattern of infiltrates on chest imaging. Finally and most promisingly, biologic subphenotypes or endotypes have increasingly been identified using plasma biomarkers, genetics, and unbiased approaches such as latent class analysis. The potential of precision medicine lies in identifying novel therapeutics aimed at ARDS biology and the subpopulation within ARDS most likely to respond. In this review, we discuss the challenges and approaches to subphenotype ARDS into clinical, radiologic, severity, and biologic phenotypes with an eye toward the future of precision medicine in critical care.
Keywords: acute respiratory distress syndrome; acute lung injury; phenotype; precision medicine